S117 The effect of cigarette and electronic cigarette vapour on bacteria in chronic lung infection. (15th November 2017) - Gilpin, DF; McGown, KA; Gallagher, K; Bengoechea, J; Elborn, JS; Tunney, MM
Abstract : Introduction: Cigarette smoke is a risk factor for the development of several chronic lung diseases, e.g., Chronic Obstructive Respiratory Disease (COPD) and bronchiectasis. This study aims to determine the effect of cigarette smoke and electronic cigarette vapour, on key bacteria involved in the progression and exacerbation of chronic lung disease. Methods: Cigarette smoke extract (CSE) and electronic cigarette vapour extract (ECVE) were prepared using a modified syringe driver apparatus and bubbling through appropriate growth media. Reference isolates [ Haemophilus influenzae, ATCC49766 (HI), Streptococcus pneumoniae ATCC49619 (SP), Staphylococcus aureus ATCC29213 (SA) and Pseudomonas aeruginosa ATCC 27853 (PA)] were grown in broth +/-CSE or ECVE. Biofilm formation and survival in the Galleria mellonella infection model, following bacterial exposure to CSE/ECVE were determined. Levels of IL-8 and TNFα secretion from A549 cells, following infection by bacteria+/-CSE/ECVE and addition of cell-signalling inhibitors, were measured by ELISA. Results: A trend towards increased biofilm formation following exposure to either CSE or ECVE was observed, which reached statistical significance with SP and PA +CSE (p=0.0047 and 0.0043, respectively) and SA+ECVE (p<0.001). There was decreased survival of Galleria mellonella following infection with bacteria+CSE/ECVE vs. bacteria only, suggestive of increased virulence; this was statistically significant in the case of HI (p=0.016) and PA (p=0.0005)+CSE. Statistically significant increases in IL-8 secretion in A549 cells were observed for HI and PA +CSE and SA+ECVE, and in TNFα, with SP and SA+ECVE. However, a clear trend towards increases in both cytokines following CSE/ECVE exposure was evident, with little difference observed between CSE/ECVE. Addition of pathway inhibitors following A549 cell infection with bacteria+CSE/ECVE resulted in a decrease in IL-8 or TNFα via the same pathways as with bacteria alone. Conclusion: Exposure of bacteria involved in the pathogenesis of chronic lung infection to both CSE and EVCE resulted in increased virulence, biofilm formation, and inflammation, and may contribute to establishment of chronic infection and persistence. Further work is required to determine the clinical effects of ECVE.